VIOLENCE IN SPORT AS RESEARCH DIRECTION OF SPORTS CRIMINOLOGY - Kipāne, Aldona (Administrative and Criminal Justice, 2018)
In today’s world the nature of violence and prevalence of it are with a high-risk profile and the nature of public safety hazard. According to its structure, violence is not uniform. It has different forms. Violent behaviour often occurs in all areas of human activity. One of such areas is sport. Violence in sport is existing criminological phenomenon, which is determined by complex and hierarchically subordinated factors.Aim is to describe the criminological aspects of the violence in sports. Research methods: theoretical studies, scientific literature analysis, statistical data analysis, data collection, systematization, analysis and synthesis.The author concludes that sport criminology should be developed in the framework of criminology in Latvia. Criminological research of sports sphere have to be promoted where the problematics, which occur in modern changing environment and affect sports industry, are analysed more widely and comprehensively. It is of great importance and vital:1) to identify the current situation, as well as to carry out an adequate and independent, and dynamic assessment of violence risks;2) to predict the future development trends of criminal situation;3) to develop preventive mechanism of negative consequences.